The Influence of Creativity and Employee Engagement on Employee Performance at PT. Karya Bahana Media Televisi Bekasi in West Bekasi - Odang Kusmayadi; Assyifa Mulandar (International Journal of Education, Information Technology, and Others, 2023)
Employee performance at PT Karya Bahana Media Bekasi can be influenced by many factors, including creativity and employee involvement. The better the creativity and involvement of employees, the better the enthusiasm and dedication of these employees so that it will improve the performance of employees of PT Karya Bahana Media Televisi Bekasi. This performance appraisal is very important to determine whether the company will continue to work with employees if their performance is good. This study aims to determine the effect of creativity and employee involvement on employee performance at PT Karya Bahana Media Televisi Bekasi. Based on the results of this study, the partial effect of the Creativity variable or X1 on Performance or Y has a value of 40.2%, then the performance variable or X2 on Performance has a value of 59.1%. The results of the research variables on creativity and employee involvement jointly affect performance by 57.5%. This means that together creativity and employee involvement have an influence of 57.5% on the performance of KBM TV Bekasi employees, while the remaining 42.5% is influenced by other variables outside the research.